The Experimental-Based Visual Auditory Kinesthetic (Vak) Learning Model Improves Elementary School Science Learning Outcomes - Putu Krisna Dewi; I Gusti Ayu Tri Agustiana; Putu Ari Dharmayanti (Mimbar Ilmu, 2023)
If the teacher only applies the lecture method, science learning is complex for students to understand. This study aimed to analyze the effect of the experimental-based VAK learning model on science learning outcomes in fifth-grade elementary school students. This research belongs to the quasi-experimental research (Quasi Experiment). The research design is the Non-Equivalent Post-test Only Control Group Design. The research population totaled 172 students. This research will use a random sampling technique. The research sample was 62 students. The data collection method used is the test method. The research instrument was a multiple-choice question sheet. The data analysis technique used is descriptive statistics and inferential statistics. The results of this study show a significant influence of the experimental-based Visual Auditory Kinesthetic (VAK) learning model on the science learning outcomes of fifth-grade elementary school students. It was concluded that the Experiment-based Visual Auditory Kinesthetic (VAK) learning model could improve the science learning outcomes of fifth-grade elementary school students. The VAK learning model can help students and make science learning fun.